Implementation of Graduate Competency Standards in the Transformation of Graduate Quality at PKBM Bina Ilmu, Rokan Hulu Regency - Adibah Feikha Naylah; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the implementation of Graduate Competency Standards (SKL) in transforming the quality of graduates at Community Learning Center (PKBM) units in Rokan Hulu Regency, Riau Province, focusing on PKBM Bina Ilmu in Pasir Pengaraian. The research employs a descriptive qualitative approach with data collected through in-depth interviews, participatory observation, and document analysis. Key informants comprising PKBM administrators, tutors, and learning participants were selected through purposive sampling. Findings reveal that SKL implementation at PKBM Bina Ilmu references Permendikbudristek Number 5 of 2022, updated by Permendikdasmen Number 10 of 2025, covering three core dimensions: attitudes, knowledge, and skills. Quality control is enacted through authentic assessment systems including portfolio evaluation, performance assessment, and continuous attitudinal assessment. Key challenges include diverse learner backgrounds, limited tutor competence, and facility disparities between urban and remote areas. The synergy of national regulation, flexible agro-industry-based local curriculum, and transformative leadership proves critical to SKL achievement. This study recommends strengthening sustainable internal quality assurance systems (SPMI) and enhancing tutor capacity as strategic measures to improve the competitiveness of non-formal education graduates in Rokan Hulu.